Thalictrum jilongense and T. tenuicaule (Ranunculaceae), described from China, are both merged with T. leuconotum - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2021)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Thalictrum jilongense and T. tenuicaule (Ranunculaceae), described from southern Xizang (Tibet) and western Sichuan, China, respectively, are both conspecific with T. leuconotum. We therefore reduce T. jilongense and T. tenuicaule to the synonymy of T. leuconotum herein. Lectotypification is proposed for T. leuconotum.